2017
DOI: 10.7880/abas.0170410a
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Existing Design for Establishing the Dominant “Industrial” Design

Abstract: Digital cameras were initially developed as video memo devices and televisions with cameras and had appearances and designs that differed from film-based cameras. However, improvements in pixel number led to them becoming replacements for film-based cameras. Radical innovations, such as the function of optical zoom and image stabilization that were required to take quality photographs, were then developed. At the same time, digital cameras took on the appearance of film-based cameras, leading to frame that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Therefore, this paper reviewed articles on design thinking. The results showed that (a) while existing review 1 Design management has become popular also in Japan in recent years (e.g., Akiike, 2017;Akiike & Yoshioka-Kobayashi, 2017;Akiike, Yoshioka-Kobayashi, & Katsumata, 2019;Hanahara, 2021). 2 (i), (ii), and (iii) are the authors' classification.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this paper reviewed articles on design thinking. The results showed that (a) while existing review 1 Design management has become popular also in Japan in recent years (e.g., Akiike, 2017;Akiike & Yoshioka-Kobayashi, 2017;Akiike, Yoshioka-Kobayashi, & Katsumata, 2019;Hanahara, 2021). 2 (i), (ii), and (iii) are the authors' classification.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies on this in the field of technology management. However, while much of the existing research has debated the technological and functional sides of dominant design (e.g., Tushman & Anderson, 1986), little analysis has been on the appearance side of dominant design, or dominant industrial design (Akiike & Yoshioka-Kobayashi, 2017). Then, does dominant industrial design have an impact on the competitive position of firms just as it does on technology (e.g., Tushman & Anderson, 1986)?…”
Section: Existing Researchmentioning
confidence: 99%